Modeling economic growth in contemporary Belarus - Sergi, Bruno S. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Since 1991, the eyes of the world have been on the economic growth and development of the states that formerly made up the Soviet Union. Looking at Belarus's industrial structure, economic growth, and economic prospects, this edited collection analyses why Belarus is considered ahead of many of its neighbour states in terms of human development. Looking across both medium- and long-term economic growth, editor Bruno S. Sergi brings together a cast of expert contributors to analyse the foreign and domestic policies that affect Belarus's economy. Across the 20 chapters included in the book, the contributors explore the largest industries in Belarus, including the financial, technology, tourism, and energy industries. With chapters on foreign investments, exports and imports, and regional policy, this is a text that looks across the whole breadth of the economy. Finally, the contributors suggest factors to increase the growth of Belarus's economy, such as launching smart cities, expanding logistic services and the tourism and hospitality industry, and the modernization of the agrarian sector.For students and researchers in political economy, or international economics, this is a vital text exploring an important, but underrepresented, economy.
Prelims -- Chapter 1 Belarus in Global Ratings: Position and Dynamics -- Chapter 2 FinTech and Commercial Banking Development in Belarus -- Chapter 3 Future of the Belarusian IT Sector: From IT Outsourcing to Industry 4.0? -- Chapter 4 Industrial Development, Structural Changes, and Industrial Policy in Belarus -- Charter 5 Technological Parks, Clusters, and Innovation Networks: Expected Transformation of Innovative Sector -- Chapter 6 Belarus on the Way to Sustainable Development: Circular Economy and Green Technologies -- Chapter 7 Changes in Fuel and Energy Industry: What to Expect after the Launch of Belarusian Nuclear Power Plant? -- Chapter 8 Agrarian Sector: Trends, Scenarios, Policy -- Chapter 9 How to Make Money on Geography: Transportation and Logistics Services in Belarus -- Chapter 10 The Development of the Tourism and Hospitality Industry -- Chapter 11 Education and Innovation Growth: Establishing Entrepreneurial Universities -- Chapter 12 PublicPrivate Partnerships and Social Innovation in Belarus -- Chapter 13 Administrative Arrangement, Spatial Development, and Regional Policy in Belarus -- Chapter 14 Smart Cities -- Chapter 15 What Belarus Produces, Exports, and Imports: Analyzing Trade in Value Added -- Chapter 16 Foreign Investments and TNCs -- Chapter 17 The Policy of the National Bank of the Republic of Belarus to Ensure Financial Stability: Achievements, Problems, and Prospects -- Chapter 18 Improving Fiscal Policies: Evolution or Revolution? -- Chapter 19 Economic Growth in Belarus: Analysis, Forecasts, and Scenarios -- Chapter 20 Foreign Economic Policy of Belarus: Integration and Multivector -- Index.
Includes index.
Keywords: Economic development -- Belarus; Business & Economics -- Economics -- General; Economic growth